2001
DOI: 10.24452/sjer.23.3.4615
|View full text |Cite
|
Sign up to set email alerts
|

Anchored Instruction: Situiertes Lernen in multimedialen Lernumgebungen

Abstract: «Anchored Instruction» ist ein konstruktivistischer Ansatz aus den USA, dessen Vertreter technologisch unterstützte, situierte Lernumgebungen für verschiedene schulische Fächer und Altersstufen entwickeln, implementieren und erforschen. Wichtige Ziele, Gestaltungsprinzipien und Merkmale solcher Lernumgebungen sowie ihre Implementation im Unterricht werden anhand von zwei Anwendungen näher dargestellt: (1) «The Adventures of Jasper Woodbury», eine Serie von Video-Geschichten und Zusatzmaterialien, die Schüler m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Scharnhorst, U. [22], believed that anchored instruction is an American constructivism method. Results showed that it is necessary to strengthen learning effectiveness evaluation as the last link in an anchored instruction environment, thus forming a closed loop in the teaching process.…”
Section: H2: Problem Identification Of Anchored Instruction Can Impro...mentioning
confidence: 99%
“…Scharnhorst, U. [22], believed that anchored instruction is an American constructivism method. Results showed that it is necessary to strengthen learning effectiveness evaluation as the last link in an anchored instruction environment, thus forming a closed loop in the teaching process.…”
Section: H2: Problem Identification Of Anchored Instruction Can Impro...mentioning
confidence: 99%
“…In Anlehnung an Monte-Sano und Budano ( 2013 (Eichner et al ., 2019;Hammond & Gibbons, 2005;Lepper & Wolverton, 2002;Scharnhorst, 2001) .…”
Section: Lernförderliche Lehrpersonenhandlungen Im Geschichtsunterrichtunclassified